2018
DOI: 10.4236/nm.2018.94020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Associated with Mortality Related to Stroke in Bangui (Central African Republic)

Abstract: Stroke is a very common neurological condition that causes permanent disability in half of the cases, at least in sub-Saharan Africa. They represent the second most common cause of death in Africa. Objective of this study was to evaluate the prognostic value of the intake period of patients suffering from these conditions on the survival time of one month of hospitalization in hospitals in Bangui. We conducted a prospective study cross prognostic kind in the neurology departments, internal medicine and intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This may testify to the ignorance of the population regarding this condition. This calls into question the need to carry out awareness-raising activities in order to enlighten the population in order to reduce the harmful consequences that may result from it [29].…”
Section: Discussionmentioning
confidence: 99%
“…This may testify to the ignorance of the population regarding this condition. This calls into question the need to carry out awareness-raising activities in order to enlighten the population in order to reduce the harmful consequences that may result from it [29].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-six studies [11,24-26,28-31, 34-37,39-48,50,52,53,55-61,63-69,71-76,78-93,96,98-104,106-108,110,111,113,114] showed low risk of bias and seventeen studies [27,33,38,37,49,51,54,62,70,77,94,95,97,105,109,112,115] showed moderate risk of bias. Twenty-two studies [26,29,32,34,39,41,46,48,50,60,61,67,68,75,76,83,85,86,92,98,110,111] had the highest overall score. One study Ukoha et al, [70] had the lowest overall score.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
“…In sub-Saharan Africa, stroke is a double burden of morbidity and mortality due to a lack of appropriate infrastructure, of awareness among populations about stroke, and care that is often expensive and not accessible to all. Stroke-related mortality is poorly described in the sub-Saharan literature, the few conducted studies show high mortality rates notably, 24.04% in Burkina Faso [9], 26.8% in Cameroon [10], and 29.9% in Bangui [11] and is probably underestimated, seeing that the majority of patients in sub-Saharan Africa turn to traditional medicine [12]. In industrialized countries, however, the recourse to traditional medicine has been declining since the introduction of stroke dedicated centres known as "neurovascular units".…”
Section: Introductionmentioning
confidence: 99%
“…In industrialized countries, however, the recourse to traditional medicine has been declining since the introduction of stroke dedicated centres known as "neurovascular units". In Gabon, non-communicable diseases (NCDs) were responsible for 6,500 deaths and accounted for 21% of the risk of premature death in 2022 [11]. Essola et al (2017) found that stroke was the leading cause of medical death in the intensive care unit of Libreville University Hospital [13].…”
Section: Introductionmentioning
confidence: 99%